Impact of education levels on economic growth in Malaysia: a gender base analysis - Nirmal Kaur Hari Singh,; Lai, Wei Sieng; Mohd Nasir Mohd Saukani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Education has been recognised as a powerful tool in boosting growth and development, and is expected to propel nation towards becoming a developed and high-income country in the near future. This paper aims to examine the impact of different levels of education, namely primary, secondary and tertiary, on economic growth in Malaysia. As a step further, the education variables are analysed by gender to examine whether the impact of education differs according to gender. The study employed the Auto-Regressive Distributed Lag (ARDL) modelling in analysing the long-term and short-term effects of education levels on economic growth, covering a period of 36 years from 1980-2015. Cointegration between all education variables and economic growth are found in this study. Overall, in the short run, tertiary education is most important to growth, while both primary followed by tertiary education were seen as growth-inducing factors in the long-run. Analysis by gender shows that in the long run, it is the male’s education that has a higher contribution to growth compared to the female. Meanwhile, in the short run, it is the female that has a higher contribution to growth than the male. Thus, both male and female should have equal opportunity on acquiring education. The government needs to ensure the equitable access and parity are achieved between both genders at schools. Since the education of the male has a positive and significant contribution in the long-run, special attention needs to be given to the enrolment rates of the males.